Characterization of tyrosinase inhibitory constituents from the aerial parts of Humulus japonicus using LC-MS/MS coupled online assay. Issue 2 (15th January 2018) - Yang, Hyo Hee; Oh, Kyung-Eon; Jo, Yang Hee; Ahn, Jong Hoon; Liu, Qing; Turk, Ayman; Jang, Jae Young; Hwang, Bang Yeon; Lee, Ki Yong; Lee, Mi Kyeong
Graphical abstract: Highlights: The aerial parts of Humulus japonicus showed tyrosinase inhibitory activity. HPLC-MS/MS coupled online tyrosinase assay of H. japonicus was performed . Twenty-eight constituents and their tyrosinase inhibitory activity were predicted. Fractionation of H. japonicus yielded thirty-eight compounds including two new compounds. Constituents and tyrosinase inhibition were well matched with HPLC-MS/MS coupled assay. Abstract: In the screening of natural products for the development as cosmetic ingredients, the EtOAc-soluble fraction of Humulus japonicus showed tyrosinase inhibitory activity. HPLC-MS/MS coupled online tyrosinase assay of EtOAc-soluble fraction of H. japonicus characterized the twenty-eight constituents including two unknown ones and their tyrosinase inhibitory activity. Fractionation of H. japonicus using various chromatographic techniques yielded thirty-eight compounds. The chemical structures of isolated compounds were identified by spectroscopic analysis. As characterized by HPLC-MS/MS analysis, we isolated twenty-four predicted compounds and further identified two unknown ones, named humulusides A (1 ) and B (2 ). Additional ten compounds were also identified by purification. Tyrosinase inhibitory activity of isolated compounds were evaluated, which was closely correlated with the results from HPLC-MS/MS coupled online tyrosinase assay. Consistent with predicted data, two major compounds, trans - N -coumaroyltyramine (14 ) and cis - N -coumaroyltyramine (15 ) showed tyrosinase inhibition with IC50 values of 40.6 and 36.4 μM. Taken together, H. japonicus is suggested as whitening ingredient in cosmetic products. In addition, HPLC-MS/MS coupled tyrosinase assay is powerful tool for predicting active compounds with short time and limited amounts, although identification of new compounds and verification of predicted data are also needs to be demonstrated by further experiment.